Building the Brand Image: An Empirical Examination of Antecedents and Consequences - Nadia Ika Purnama; Nel Arianty; Novien Rialdy (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
This study aims to analyze the effect of service quality on student satisfaction and its impact on the brand image of private universities in North Sumatra, with word of mouth (WOM) as a mediating variable. This study uses a quantitative approach with a survey method of active students from several private universities. The results of the analysis show that service quality has a significant effect on student satisfaction; satisfaction affects brand image; and WOM affects brand image. In addition, WOM has been shown to mediate the effect of satisfaction on brand image. This finding confirms that student satisfaction directly impacts brand image and WOM, an influential informal communication channel. This research provides theoretical contributions to the development of consumer behaviour models in the higher education sector and practical implications for higher education management to improve services and strengthen the institution's image.